Pathophysiology of cataracts - Alamri, Mohammed; Alsammahi, Alaa; Alharbi, Majid; Alshammari, Hamad; Alshehri, Mousa; Saeedi, Ibrahim; Alhomoud, Maher; Albakri, Ismaeel; Alwagdani, Hadeel; Bin Yousef, Khaled (International Journal Of Community Medicine And Public Health, 2018)
Cataracts result in significant vision reduction. It is estimated that cataract was responsible for the morbidity of 10.8 million people (of overall 32.4 million blind people around the world), and 35.1 million people (of overall 191 million vision impaired people around the world). It is also the most common cause of blindness in many countries, including Saudi Arabia. We tried to understand, in details, the pathogenesis of cataracts, with special focus on how ageing is a contributory factor in its development. We conducted this review using a comprehensive search of MEDLINE, PubMed and EMBASE from January 1970 to March 2017. The following search terms were used: cataracts, pathogenesis of cataracts, pathophysiology in cataracts, ageing lens, aging and vision loss, lens degeneration. Cataracts heavily impacts the vision, thereby, the lives of individuals suffering from it. Due to its large prevalence, the impact on economy is large too. Although surgery is very promising, newer approach is focusing on its pathophysiology to emphasize on preventive options. Several changes, including oxidative stress, reduction in reductive enzymes, lens elasticity, and specific age related degeneration play major roles in its pathophysiology.